Experimental Comparison of Piezoelectric Rectifying Circuits for Energy Harvesting - Mustapha, Ain Atiqa; Mat Ali, Noraini; Kok, Swee Leong (2013)
Piezoelectric energy harvester transforms mechanical energy into electrical energy. However, the electrical output purely from the energy harvester needed to be conditioning before being use to power up small electronic devices. Output voltage in AC form will need to be rectified followed by stepping down using DC-DC converter to voltage level suit to any desired application. In this paper, an experimental was carried out to compare two different integrated circuit based rectifiers one of which is constructed using low voltage drop Schottky diodes, BAT754L and the other one is glass passivated single-phase bridge rectifier, W08G. It has been verified with experiment that Schottky diode outperformed normal diode type rectifying circuit.